Information Technology-based Interventions for Health Care Support in Patients with Chronic Kidney Disease: A Systematic Review - Inda Rian Patma Putri; Nursalam Nursalam; Ninuk Dian Kurniawati (Jurnal Ners, 2019)
Background: Self-management and support in managing therapeutic regimens is very important for patients with CKD. Information technology-based interventions are increasingly being used to support the self-management of patients with CKD. This study aimed to conduct a systematic review to evaluate information technology-based interventions in relation to the support of the health management of patients with CKD.Method: We conducted a systematic review using electronic databases (Scopus, Science Direct, ProQuest) limited to the last 8 years from 2010 to 2018 with the relevant keywords. The studies included used RCT, pilot and case-control methods focusing on patients with CKD stage 1-5 and that reported on at least one outcome from the health management of patients with CKD.Result: Out of the 7.852 studies taken, 13 studies fulfilled the inclusion criteria. The interventions in this systematic review are multifaceted, including smartphone/PDA (6/13), telematics devices (2/13), internet/web (3/13) and a combination of several interventions (2 studies). In total, 12 (92%) out of the 13 studies showed a positive outcome from the intervention, 7 studies showed improved outcomes in the clinical points, 3 studies had improved adherence and 2 studies improved knowledge.Conclusion: This evidence indicates the potential of IT-based interventions (i.e. smartphone/PDA, computer, internet/web, telematic device) to support the health management of patients with CKD. The variety of interventions in this systematic review requires further research on which interventions are best applied.